SUITABILITY OF GREEN ECONOMY WITH ISLAMIC ECONOMY TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS - Fadila, Nisa Rahma; Kasmiarno, Kurnia Sari (Az-Zahra Media Society, 2026)
Global warming and climate change, driven by exploitative economic systems, have heightened the urgency of economic restructuring toward a green paradigm. This research aims to examine the suitability of the green economy concept and Islamic economic principles within the framework of achieving the Sustainable Development Goals (SDGs). Using the library research method with content analysis techniques, this study analyzes the alignment of the green economy in three main clusters of Islamic economics, namely: Islamic finance, Islamic social finance (Ziswaf), and Islamic business. The results of the study show that Islamic economics provides an ethical foundation through the concept of khalifah fil 'ardh and fiqh al-bi'ah which prohibits environmental destruction and emphasizes ecological responsibility. In the financial cluster, green sukuk instruments have emerged as innovative funding solutions for environmentally friendly projects that meet sharia principles. In the social finance sector, the use of Ziswaf, including the cash waqf-linked blue sukuk, has proven to be effective in supporting nature conservation as well as poverty alleviation. The integration of Islamic business with the green economy encourages the creation of green entrepreneurship (ecopreneurship) that prioritizes resource efficiency and zero-waste systems. This research concludes that the synergy between the green economy and Islam offers an inclusive and sustainable development model for the benefit of future generations.